A Preliminary Study on the Effects of Nitrite Exposure on Hematological Parameters, Oxidative Stress, and Immune-Related Responses in Pearl Gentian Grouper - Hongzhi Zhang; Dan Fang; Jun Mei; Jing Xie; Weiqiang Qiu (Fishes, 2022)
Nitrite represents one of the most typical contaminants in aqueous species. The research was conducted to evaluate the impacts of nitrite exposure on the survival, gill morphology, hematological parameters, immune response, and meat flavor of pearl gentian grouper. The fish were exposed to 0, 5, 10, and 20 mg/L of nitrite for 96 h (note: N-0, N-5, N-10, and N-20 indicate nitrite concentrations of 0, 5, 10, and 20 mg/L, respectively). The blood, gills, and muscles were collected from fish to determine hematological parameters, immune response, oxidative stress, and meat flavor after 0, 12, 24, 36, 48, 60, 72, and 96 h of exposure. The data showed that the aspartate aminotransferase (AST), cortisol (COR), malondialdehyde (MDA), alanine aminotransferase (ALT), alkaline phosphatase (AKP), and free amino acids (FAAs) contents were significantly increased, while the glutathione (GSH), immunoglobulin M (IgM), superoxide dismutase (SOD), and lysozyme (LZM) contents were remarkably declined in the N-20 group after 72 h of exposure. In gills, exposure to the higher concentrations of nitrite resulted in the proliferation and hypertrophy of epithelial cells of gill lamellae, as well as an increase in mucous cells. In addition, all fish in the N-10 and N-20 groups died after 96 h of exposure. Our findings suggested that exposure to higher concentrations of nitrite disrupted blood physiology and oxidative stress, leading to dysfunction in the pearl gentian grouper.